2021
DOI: 10.1128/msphere.00412-21
|View full text |Cite
|
Sign up to set email alerts
|

Clover Root Exudates Favor Novosphingobium sp. HR1a Establishment in the Rhizosphere and Promote Phenanthrene Rhizoremediation

Abstract: The success of an eco-friendly and cost-effective strategy for soil decontamination is conditioned by the understanding of the ecology of plant-microorganism interactions. Although many studies have been published about the bacterial metabolic capacities in the rhizosphere and about rhizoremediation of contaminants, there are fewer studies dealing with the integration of bacterial metabolic capacities in the rhizosphere during PAH bioremediation, and some aspects still remain controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…In our study, we have found that planting, addition of maltose and glycine can significantly facilitate the degradation of petroleum hydrocarbons in loamy soil and clayey soil. Molina et al (2021) found that the maltose concentration in the clover root exudates with bacterial presence was significantly lower than that of the exudates without bacteria. Maltose can enhance the degradation of total petroleum hydrocarbons, probably because it can provide a large amount of energy and nutrient source for rhizosphere microorganisms, increasing the density and of microorganisms (Al-Ali et al, 2018) and then promoting the removal of petroleum hydrocarbon in soil.…”
Section: Removal Effect Of Root Exudates On Total Petroleum Hydrocarb...mentioning
confidence: 87%
“…In our study, we have found that planting, addition of maltose and glycine can significantly facilitate the degradation of petroleum hydrocarbons in loamy soil and clayey soil. Molina et al (2021) found that the maltose concentration in the clover root exudates with bacterial presence was significantly lower than that of the exudates without bacteria. Maltose can enhance the degradation of total petroleum hydrocarbons, probably because it can provide a large amount of energy and nutrient source for rhizosphere microorganisms, increasing the density and of microorganisms (Al-Ali et al, 2018) and then promoting the removal of petroleum hydrocarbon in soil.…”
Section: Removal Effect Of Root Exudates On Total Petroleum Hydrocarb...mentioning
confidence: 87%
“…Total RNA extraction and preparation of libraries were carried out as in Molina et al (2021) . Briefly, the RNA was extracted using the Trizol method (TRIzol RNA Isolation Reagents, Thermofisher Scientist), followed by DNAse treatment and purification with the RNeasy Mini Kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…Novosphingobium sp. HR1a is able to degrade low-, medium- and high-molecular weight polycyclic aromatic hydrocarbons ( Segura et al, 2017 ), and it has shown excellent potential for rhizoremediation ( Molina et al, 2021 ). Furthermore, this strain is able to grow in marine media ( Segura et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these enzymes catalyse the oxidation of phenolic compounds and PAHs using hydrogen peroxide as the electron acceptor, transforming these molecules into more easily degradable compounds for the indigenous microbiota, and therefore, indirectly, detoxifying these environments. Similarly, root exudates of various plant species, such as fescue grass (Festuca arundinacea), switch grass (Panicum virgatum), maize (Zea mays L.), soybean, sorghum, alfalfa and clover, have the ability to enhance PAH biodegradation, probably because plant roots can stimulate soil microbial biomass and oxygen transport to the rhizosphere, thus facilitating the degradation process [113,114].…”
Section: Detoxification Of Pahs and Hms By Plantsmentioning
confidence: 99%